2014
DOI: 10.1111/jgs.13068
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging Findings in Elderly Adults and Years of Life, Healthy Life, and Able Life over the Ensuing 16 Years: The Cardiovascular Health Study

Abstract: OBJECTIVES To determine whether elderly people with different patterns of MRI findings have different long-term outcomes. DESIGN longitudinal cohort study. SETTING the Cardiovascular Health Study. PARTICIPANTS 5,888 people over age 65 were recruited; 3,660 underwent MRI; and 3,230 without a stroke prior to the scan were included in these analyses. MEASUREMENTS Cluster analysis of brain MRI findings was previously used to define five clusters: Normal, Atrophy, Simple Infract, Leukoaraiosis, and Complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…For all other time points, 0.3% to 12.5% of ADL data were missing and were also imputed. This method of imputation of CHS data has been previously described . Remaining YAL for 544 participants who survived to the end of follow‐up was imputed using regression equations .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all other time points, 0.3% to 12.5% of ADL data were missing and were also imputed. This method of imputation of CHS data has been previously described . Remaining YAL for 544 participants who survived to the end of follow‐up was imputed using regression equations .…”
Section: Methodsmentioning
confidence: 99%
“…This method of imputation of CHS data has been previously described. 14,15 Remaining YAL for 544 participants who survived to the end of follow-up was imputed using regression equations. 13 YAL/YoL% was calculated to represent the relative proportion of the observed life span that was lived free of ADL difficulty.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…7,[31][32][33]95 In the prospective Cardiovascular Health Study, the combination of WMHs and infarcts carried the worst prognosis with regard to long-term survival, self-rated health, and limitation in activities of daily living (ADLs). 96 In the Rotterdam Scan Study, progression of WMHs in the periventricular regions was paralleled by declines in information processing speed and general cognition, as well as decline on the MMSE. 28 The LADIS study reported 2.4-year followup data for its observational cohort of 633 older people, and found a transition rate of 29.5% to death or disability in ADLs for those with severe WMH (Fazekas 3) at entry, compared with 10% in those with only mild changes.…”
Section: Wmhs and The Development Of Dementiamentioning
confidence: 99%
“…White matter hyperintensities (WMHs) are common brain magnetic resonance imaging (MRI) changes in the elderly and play an important role in their quality of daily life. 1 WMHs are usually located in basal ganglia, periventricular, subcortical or semioval center regions, caused by demyelination and axonal loss resulting from cerebral small vessel disease. 2,3 Many studies suggested that WMHs were associated with cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%